MORPHOFUNCTIONAL INDICATORS OF 9-12 YEAR-OLD CANOE AND KAYAK ROWERS - Vladimir Davydov; Vladimir Shantarovich; Aleksandr Zhuravskiy; Dmitriy Prigodich (Lesya Ukrainka Volyn National University, 2017)
The problem of selecting young canoe and kayak rowers can not be successfully solved unless the medical and biological aspects are subjected to a thorough analysis. The basis of individual differences of development and improvement preconditions of the sportsman's motor abilities is his morphological features. For kayaking and canoeing, the most informative are the following indicators: body length, arm length, arm spread, body length, when kneeling with arms outstretched, body length when sitting arms up and body length up to the 7th cervical vertebra.